Calling on the EU-US Trade and Technology Council: How to deliver for the planet and the economy - Oscar Guinea; Vanika Sharma; Philipp Lamprecht; Dyuti Pandya; Oscar du Roy (European Centre for International Political Economy (ECIPE), 2024)
This Policy Brief proposes the establishment of an agreement on conformity assessment between the EU and the US that covers machinery and electrical equipment. The initiative aims to increase the number of European and US conformity assessment bodies authorized to test and certify EU and US machinery and electrical equipment for exports into each other's markets, without recognizing the equivalency or otherwise altering the product requirements in regulation, standards, or other normative documents on either side. While this study focuses on the economic effects of an agreement on conformity assessment that includes machinery and electrical equipment, the scope of such an agreement could potentially be extended to several additional product categories, particularly those that are subject to requirements for mandatory third-party conformity assessment in both the EU and the US.
Keywords: 330; International agreement; Electrical engineering; Electronic product; Product safety; Standardization; International economic relations; International economic policy; EU countries; USA; Internationales Abkommen; Elektrotechnik; Elektronisches Produkt; Produktsicherheit; Standardisierung; Internationale Wirtschaftsbeziehungen; Internationale Wirtschaftspolitik; EU-Staaten; USA